GROWTH AND PRODUCTION OF SOYBEAN (Glycine max (L.) Merill) DUE TO APPLICATION OF AMELIORAN AND ORGANIC INGREDIENTS PALM WASTE - Parwito, Parwito; Alatas, Ali; Susilo, Edi; Pujiwati, Hesti (CROP AGRO, Scientific Journal of Agronomy, 2023)
Soybean is one of the nutritious food commodities and a source of vegetable protein whose production is still below Indonesia's domestic needs. Research needs to be done to increase soybean productivity on marginal land. This study aims to measure the growth and yield of soybeans against the application of ameliorant and organic fertilizer made from palm oil waste. The study was conducted in Gunung Alam Village from February to April 2020. The study used a randomized block design which was arranged in a factorial manner and consisted of two factors with three replications. The first factor was ameliorant, namely 0 ton.ha-1, 1 ton.ha-1, 2 ton.ha-1, and 3 ton.ha-1. The second factor is LPMKS (Palm Oil Mill Fertilizer) fertilizer, namely 0 ton.ha-1, 2 ton.ha-1, 4 ton.ha-1, and 6 ton.ha-1. The results showed that the interaction between amelioran and organic fertilizer had a significant effect on the number of leaves 49 days after planting, namely the dose of ameliorant was 2 tons.ha-1 with LPMKS fertilizer 2 tons.ha-1, which was 29.73 strands. The ameliorant treatment had an effect on the variable weight of pods per plant, and the LPMKS treatment had a significant effect on the variable age of harvest at a dose of 6 ton.ha-1, the number of pods per plant at a dose of 6 ton.ha-1, and the number of pithy pods at a dose of 6 ton.ha. -1.